CROSS-CULTURAL COMMUNICATION : A COMPARATIVE ANALYSIS OF UZBEK AND ENGLISH CULTURES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This article aims to explore the dynamics of cross-cultural communication between Uzbek and English cultures. It examines the unique characteristics, values, and communication styles in both cultures and provides an overview of the challenges and strategies for effective communication in diverse contexts. The analysis highlights the importance of cultural awareness, sensitivity, and adaptability to foster successful intercultural interactions between Uzbek and English speakers.